PENGARUH ELECTRONIC WORD OF MOUTH, SOCIAL MEDIA MARKETING, DAN PERCEIVED QUALITY TERHADAP MINAT BELI MELALUI BRAND IMAGE SEBAGAI VARIABEL MEDIASI PADA PRODUK FASHION JINISO DI PURWOKERTO - Faradila Aisya Hanifah; Tri Septin Muji Rahayu (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the impact of EWOM, social media marketing, and perceived quality on purchase intention through brand image among consumers in Purwokerto. Using a quantitative approach and SmartPLS analysis, data was collected from 150 respondents. The results show that EWOM, social media marketing, and perceived quality significantly influence both brand image and purchase intention, while brand image also has a significant positive effect on purchase intetion and mediates these relationships. These findings demonstrate the importance of strengthening digital marketing strategies and improving perceived quality to build a strong brand image and increase consumer purchase intention. Keywords: Electronic Word of Mouth; Social Media Marketing; Perceived Quality; Brand Image; Purchase Intention